B A (2, -1, 3) l : (x, y, z) = (3t, 5t - 7, 2t + 2) . l1 : r = r1 + t u l2 : r = r2 + s u, r1 = [3, 1, -1], r2 = - e1, u = [1, -1, -2] . l1 l2 2x + 3y - z - 1 = 0 x + 5y + 4z = 3 l1 : l2 : x + y - 3z = 0 x + 2y + 2z = 1 l1 : (x, y, z) = (9, -2, 0) + t (4, -3, 1) , x y + 7 z - 2 l2 : = = , -2 9 2 (x, y, z) = (3, 4, 6) + t (-5, 6, 8) XOY. A (-3, 1, -1) , B (6, -2, -5) , C (1, -2, -1) . BD B AC. A (1, 2, -1) , B (0, 1, 5) , C (-1, 2, 1) D (2, 1, 3) r = r0 + t u r ć% v = D u &" v a = p - 2 q b = 2 p + 4 q, Ą | p | = 2, | q | = 3, ( p, q) = . 3 O (0, 0, 0) , A (5, 2, 0) , B (2, 5, 0) C (1, 2, 4) . O. P (2, -1, -3) 3x - y + 2z + 2 = 0 x + 3y - 6z + 4 = 0.